An emerging deep eutectic solvent based on halogen-bonds. Issue 29 (21st March 2022) - Shi, Ruifen; Yu, Dongkun; Zhou, Fengyi; Yu, Jiangfeng; Mu, Tiancheng
Abstract : A new deep eutectic solvent (DES) driven by halogen bonding was exploited. Abstract : A new deep eutectic solvent (DES) driven by halogen bonding (XB) was exploited. A family of eutectic mixtures in the liquid state was obtained by the combination of quaternary ammonium salts and dihalogens. The formation mechanism was discussed based on experiments and DFT calculations. It not only broadens the potential DES systems but unlocks the possibility of XB complexes as solvents.